Życie innych historii - Tomczok, Paweł (Śląskie Studia Polonistyczne, 2011)
The article deals with the issue of alternative, counterfactual and non-existent stories. The first part distinguishes between literary and historiographic presentations of non-existent worlds – literary visions of alternative stories by Philip Dick or Richard Harris are confronted with texts by Niall Ferguson or Alexander Demandt. The second part discusses methodological-philosophical issues connected with writing about non-existent past while the last one was devoted to the Muse of Distant Journeys by Teodor Parnicki, a novel in which two counterfactual stories appear, a journey with a father which did not happen because of Brunon Parnicki’s death, as well as the history of the fourth kingdom when Poland won the war after the November Uprising. Parnicki uses both literary and historiographic conventions of alternative stores in his works. On the one hand, he researches the subject-matter, e.g. summarises the history of the alternative nation, and, presents episodes from a literary-political history of the fourth kingdom on the other.